THE IMPLICATION OF A CORPUS-BASED APPROACH OF SPECIALIZED VOCABULARY IN EIS COURSE INSTRUCTION AT THE UNIVERSITY LEVEL (International Conference on Social and Islamic Studies, 2021)
This research seeks to define the implications of teaching English for Islamic Studies (EIS) based specialized corpora into university-level for non-native speakers of the English language. The EIS course is one of additional course for the first year students in Islamic university especially in Universitas Islam Negeri Alauddin Makassar, Indonesia. Corpora of English for Islamic Studies were compiled from literature used in English for Islamic Studies. The vocabulary compositions and lexical density were examined. The results of this study imply that the use of corpus is very useful for studying contexts where words that have identical meanings are usually used so as to avoid and avoid unwanted connotations. In relation to teaching English equivalents, the corpus can be an effective learning medium. A lot of information not found in dictionaries can be learned using the corpus.